Nutrition, Genetics, and Cardiovascular Disease - El Ghoch, Marwan; El Shamieh, Said (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cardiovascular diseases are the first cause of death worldwide, in which genetic and environmental factors seem to play a determinant role. In fact, several lifestyle (i.e., dietary, physical inactivity) factors and nutritional-related diseases (i.e., obesity, type 2 diabetes) are strongly associated with cardiovascular diseases. Moreover, genome-wide association studies have also identified numerous genomic loci that determine susceptibility to cardiovascular events. Therefore, nutrition and genetics seem to interact in predisposing an individual to cardiovascular diseases. This book provides a presentation of recent advances in knowledge on nutrition, genetics, and cardiovascular disease coming from diverse scientific disciplines.